Regulatory orchestration of FK506 biosynthesis in Streptomyces tsukubaensis NRRL 18488 revealed through systematic analysis - Namil Lee; Woori Kim; Ji Hun Kim; Yongjae Lee; Soonkyu Hwang; Gahyeon Kim; Hyeseong Kim; Qingyun Dan; Matthias Schmidt; Yeo Joon Yoon; Suhyung Cho; Bernhard Palsson; et al. (iScience)
Summary: Streptomyces tsukubaensis NRRL 18488, the primary producer of the immunosuppressant FK506, was analyzed to elucidate regulatory features of secondary metabolism. Completion of its 7.9-Mb linear genome enabled accurate re-annotation of the FK506 biosynthetic gene cluster (BGC). Transcriptome analysis during BGC activation revealed major transcriptional shifts from primary to secondary metabolism, especially in genes involved in FK506 biosynthesis and lysine metabolism. Primary transcriptome mapping identified 1,225 transcription units and uncovered post-transcriptional regulation of allylmalonyl-CoA production, a key FK506 precursor. Ribosome profiling demonstrated that AT-rich codons reduce translational efficiency in S. tsukubaensis, with pronounced ribosome pausing at the TTA codon within the FK506 BGC. Substituting this codon relieved pausing and improved FK506 production. Together, these integrative genomic, transcriptomic, and translatomic analyses highlight how multi-level regulatory mechanisms shape secondary metabolism in Streptomyces. This work offers insights into metabolic control that could inform future efforts in strain improvement for efficient natural products production.